Health Literacy: How is it Related to Body Mass Index of Patients with Diabetes Mellitus? - Azizi, Maisarah Shaik; Vanoh, Divya; Yudin, Zainab Mat (Jurnal Gizi dan Pangan, 2022)
This study aimed to assess the level of health literacy and determines the association between health literacy and BMI among T2DM patients in Hospital Universiti Sains Malaysia (HUSM). A cross-sectional study was conducted among 96 patients with T2DM. Health literacy was measured using the Malay version of the European Health Literacy Survey Questionnaire 16 (HLS–EU–Q16).Information about sociodemographic, weight, height, and body mass index were obtained. The majority of the participants had sufficient health literacy (60.4%), whereas the mean BMI of patients was 28.59 kg/m2. A significant association was found between BMI with health literacy levels. The median BMI value of the sufficient health literacy group was significantly higher, 28.38( 6.02) than the problematic health literacy group, 25.38 (7.52) using Kruskal Wallis test. This indicates that health literacy may be a predictor of BMI. Or maybe, the other way around is true, increased BMI may result in increased awareness on health. Still, other stronger determinants besides health literacy such as income and dietary intake which were not included in this study might influence the BMI of T2DM patients.